Somewhere Beyond the Sea - Book 2 - Klune, TJ (New York : Tor/Tor Publishing Group, 2024)
"Arthur Parnassus lives a good life, built on the ashes of a bad one. He's the headmaster of a strange orphanage on a distant and peculiar island, and he hopes to soon be the adoptive father to the six magical and so-called dangerous children who live there. Arthur works hard and loves with his whole heart so none of the children ever feel the neglect and pain that he once felt as an orphan on that very same island so long ago. And he is not alone: joining him is the love of his life, Linus Baker, a former caseworker in the Department in Charge of Magical Youth; Zoe Chapelwhite, the island's sprite; and her girlfriend Mayor Helen Webb. Together, they will do anything to protect the children. But when Arthur is summoned to make a public statement about his dark past, he finds himself at the helm of a fight for the future that his family--and all magical people--deserve"--
Keywords: Magic -- Fiction; Orphanages -- Fiction; Families -- Fiction; Gay fathers -- Fiction; Foster parents -- Fiction; Islands -- Fiction; Paranormal fiction; Gay fiction; Lesbian fiction; Fantasy fiction; Romance fiction